rewrite this in simplest terms

−6 (0.6w−3w−0.9) − 0.9w

9 answers

Simplify by multiplying -6 by all the terms inside the parentheses, then subtracting 0.9w from the result.
just do it
-6(0.6w) - 6(-3w) - 6(-0.9) - 0.9w
= -3.6w + 18w + 5.4 - 0.9w
= 13.5w + 5.4
rewrite this in simplest terms
0.5 (−9y + 4y + 2) − 0.5y
To simplify, first distribute 0.5 to each term inside the parentheses, then subtract 0.5y from the result.
can you just do it
0.5(-9y) + 0.5(4y) + 0.5(2) - 0.5y
= -4.5y + 2y + 1 - 0.5y
= -2.5y + 1
it was wrong
I apologize for the mistake. Let's correct the simplification:

0.5(-9y + 4y + 2) - 0.5y
= 0.5(-5y + 2) - 0.5y
= -2.5y + 1 - 0.5y
= -3y + 1